Environtmentally healthy sleep light - Nasution, Tulus Ikhsan; Nasution, Mahyudin K.M; -, Susilawati; Azdena, Dara (Talenta Publisher, 2019)
Healthy sleep lights that will be proposed for community service are the results of research in which the use of LED lights (Light Emitting Diode) is activated with a maximum power of 3 Watts, so that the power consumed is quite low. This healthy sleep lamp also has some uniqueness such as turning on and off with sound by utilizing applications installed on smartphones. This voice control application can also be used to vary the color of the light. This lamp can be turned on and off by touching the light nest by using a sensor system and also the color and brightness of the lamp can be adjusted using the RGB control application on the smartphone. Intensity test results for LED lights 112 - 996 (Weber / m2). The standard intensity limit for healthy bulbs based on H. Steve, H. Gaube and J. Winterhager is 3,000 (Weber / m2), so that meeting the intensity standard is an LED lamp. Our long-term goal is to develop research results into products that have economic value, facilitate students to develop creativity and innovation and create jobs by partnering with partners.